THE LEARNING OF CHILDREN IN RESIDENTIAL SITUATIONS: : DIAGNOSIS AND INTERVENTION - Eugênia Fernandes do Rêgo, Magna; Gerlânia Soares Batista, Káttia (Revista Gênero e Interdisciplinaridade, 2021)
Learning problems are becoming the topic of several researches in the field of learning and human development, considering childhood as the time that requires greater investment in this psychological process with a view to greater results. Therefore, this study seeks to analyze the frequency of illiterate children from the Individual Care Plan (PIA) of a childcare facility in the city of Mossoró/RN. For this, a documentary research was carried out to collect data on the children cared for in this care, as well as a bibliographical research to study the learning process and the context of the learning problems present in vulnerable children in institutional care situations, elucidating the possible tools to overcome these difficulties. In addition to the survey that justifies more in-depth studies on the subject, a small sample of the reality of other locations (bibliographic) was collected and, at the end, strategies were presented to deal with this reality in order to modify it, such as: tutoring, which is already used in the researched host and school and host partnership. This article is an important guide to deal with this problem that sometimes appears in the field of neuropsychology, which are learning difficulties in a specific situation that is that of institutionalized children.